Cognitive Semiotics (De Gruyter Mouton, 2007)
Cognitive Semiotics is a multidisciplinary journal devoted to high-quality research, integrating perspectives, methods and insight from cognitive science, cognitive linguistics and semiotics, placing meaning-making into the broader context of cognitive, social and neurobiological processes. The journal is a platform for the study of meaning-making in our interactions with the surroundings in all domains, in language and other sign vehicles.